Selective serotonin reuptake inhibitors for unipolar depression: A systematic review of classic long-term randomized controlled trials - Deshauer, Dorian; Moher, David; Fergusson, Dean; Moher, Ester; Sampson, Margaret; Grimshaw, Jeremy (Canadian Medical Association Journal, 2008)
Background: Selective serotonin reuptake inhibitors are increasingly used in the long-term treatment of depression. Much of the supporting evidence about the effects of these drugs comes from discontinuation trials, a variant of randomized controlled trials whose design is problematic to interpret. We conducted a systematic review to examine the efficacy and acceptability of long-term therapy with selective serotonin reuptake inhibitors relative to placebo in the treatment of unipolar depression. Methods: We identified placebo-controlled randomized trials with a treatment duration of at least 6 months by searching MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials to update a recently published systematic review. Efficacy was defined in terms of response to treatment (50% improvement in depression score relative to baseline) and remission (score of 7 or below on the Hamilton rating scale for depression). Key secondary outcomes included quality of life, return to work, need for additional treatment and self-harm. Overall acceptability was defined in terms of dropouts for any reason over a course of treatment. Results: Of the 2693 records identified initially, we included 6 randomized controlled trials that met our eligibility criteria. These studies had a moderate risk of bias, had assigned a total of 1299 participants with depression to either treatment or placebo and had followed both groups for 6–8 months. We observed statistically significant improvements in response to treatment (odds ratio [OR] 1.66, 95% confidence interval [CI] 1.12–2.48), but not in remission (OR 1.46, 95% CI 0.92–2.32) or acceptability (OR 0.87, 95% CI 0.67–1.14). The effects appeared greater among patients without comorbidities. Interpretation: There is a lack of classic randomized controlled trials of serotonin reuptake inhibitors lasting more than 1 year for the treatment of depression. The results of our systematic review support current recommendations for 6–8 months of antidepressant treatment following initial recovery but provide no guidance for longer treatment. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Clinical Trials; Depressive Disorder; Drug Therapy; Drug Tolerance; Humans; Major Depression; Outcome Assessment (Health Care); Placebos; Quality of Life; Randomized Controlled Trials as Topic; Research Design; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Treatment Effectiveness Evaluation; drug acceptability; drug efficacy; long-term therapy; randomized controlled trials; selective serotonin reuptake inhibitors; unipolar depression